Urine TWEAK level as a biomarker for early response to treatment in active lupus nephritis: a prospective multicentre study - Thitima Benjachat Suttichet; Wonngarm Kittanamongkolchai; Chutipha Phromjeen; Sirirat Anutrakulchai; Thanachai Panaput; Atiporn Ingsathit; Nanticha Kamanamool; Vuddhidej Ophascharoensuk; Vasant Sumethakul; Yingyos Avihingsanon (Lupus Science and Medicine)
Background TNF-like weak inducer of apoptosis (TWEAK) is a proinflammatory molecule that plays a key role in active inflammation of lupus nephritis (LN). Urine TWEAK (uTWEAK) levels were found to be associated with renal disease activity among patients with LN. Here, we determined whether serial measurements of uTWEAK during induction therapy could predict treatment response or not.Methods Spot urine samples were collected from patients with biopsy-proven active LN at time of flare, and 3 and 6 months after flare to assess the uTWEAK levels. All patients received standard immunosuppressive therapy and treatment response was evaluated at 6 months. The performance of uTWEAK as a predictor for treatment response was compared with clinically used biomarkers for patients with LN.Results Among 110 patients with LN, there were 29% complete responders (CR), 34% partial responders (PR) and 37% non-responders (NR). On average, uTWEAK level was consistently low in CR, trended down by 3 months in PR and persistently elevated in NR. uTWEAK levels at month 3 were able to predict complete response at month 6 (OR adjusted for age, sex and creatinine=0.34 [95% CI 0.15 to 0.80], the area under the receiver operating characteristic curve [ROC-AUC]=0.68, p=0.02). The optimal threshold for uTWEAK level at month 3 was 0.46 pg/mgCr, discriminating complete response with 70% sensitivity and 63% specificity. Combining uTWEAK and urine protein at month 3 improved predictive performance for complete response at 6 months (ROC-AUC 0.83, p<0.001).Conclusions In addition to urine protein, uTWEAK level at 3 months after flare can improve the accuracy in predicting complete response at 6 months of induction therapy.